Prospects and progress of DNA vaccines for treating hepatitis B. (3rd May 2016) - Chen, Margaret; Jagya, Neetu; Bansal, Ruchi; Frelin, Lars; Sällberg, Matti
ABSTRACT: The hepatitis B virus (HBV) is a global cause of liver disease. The preventive HBV vaccine has effectively reduced the disease burden. However, an estimated 340 million chronic HBV cases are in need of treatment. Current standard therapy for chronic HBV blocks reverse transcription. As this therapy blocks viral maturation and not viral protein expression, any immune inhibition exerted by these proteins will remain throughout therapy. This may help to explain why these drugs rarely induce off-therapy responses. Albeit some restoration of immune function occurs during therapy, this is clearly insufficient to control replication. Central questions when considering therapeutic DNA vaccination as an addition to blocking virus production are as follows: what does one hope to achieve? What do we think is wrong and how can the vaccination correct this? We here discuss different scenarios with respect to the lack of success of tested DNA vaccines, and suggest strategies for improvement.